Service Quality Terhadap Loyalitas Pelanggan Online Melalui Kepuasan Pelanggan Pengguna Layanan Aplikasi Grab - Indriyati Indriyati (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this study is to determine whether Service Quality could increase customer loyalty which in this study shown by Grab service customer satisfaction. This research method used path analysis techniques (path analysis). Path analysis is an extension of regression analysis, to estimate the causal relationship between pre-defined variables. The results of statistical calculations show that the Service Quality variable has a significant effect on the Customer Satisfaction variable with a coefficient value of 0.893 and a significant effect on the Customer Loyalty variable with a coefficient value of 0.204. Moreover, the Customer Satisfaction variable has a significant effect on the Customer Loyalty variable with a coefficient value of 0.668. Based on those results, the Service Quality has a significant effect on Customer Loyalty with a path coefficient of 0.204 and a significant value of 0.000 (sig probability <0.05). The other result of indirect testing effect between the Service Quality on Customer Loyalty through Customer Satisfaction shows the path coefficient of 0.596524 which means the indirect effect is significant. Thus, it could be concluded that the Service Quality could increase Customer Loyalty or act as a mediating variable.